Impacts of short-term wind events on Chukchi hydrography and sea-ice retreat. (May 2022) - Lu, Kofan; Danielson, Seth; Weingartner, Thomas
Abstract: We seek a better understanding of the summer ice retreat over the Chukchi shelf in the presence of a warm background inflow by investigating mechanisms through which wind forcing mediates changes in sea-ice cover, water-column hydrography, and their inter-related evolution in time. The problem is addressed with observations and an idealized representation of the Chukchi Sea's Central Channel within the Regional Ocean Modeling System (ROMS). An inflow from the south, surface heat fluxes, and wind forcing drives the numerical model. Due to strong atmosphere-ice coupling, direct wind-forced advection of the ice edge emerges as an important factor that controls the oceanic response, including corresponding alterations of the sea surface height. Surprisingly, we find no significant wind control of the cross-frontal eddy transport, due to counterbalancing effects of the frontal density gradient and the pycnocline depth. We propose that wind direction along with differences in the strength of atmosphere-ocean and atmosphere-ice-ocean coupling (drag coefficients) regulate the wind influence on the Chukchi Shelf summer ice retreat and hydrographic structure. Advection of ice away from the inflow reduces the ice melt rate and increases the salinity of the meltwater plume. Advection of ice toward the inflow increases the ice melt rate and decreases the meltwater plume salinity. The identified mechanisms represent steps toward a more complete understanding of the summer conditions in the Chukchi Sea and will help future investigations of seasonally ice-covered shelf ecosystems.